2020
DOI: 10.1177/2333392820941348
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Patterns of Medicaid-Eligible Women, 1999-2014: A National Prospective Longitudinal Study

Abstract: Introduction: The number and outcomes of pregnancies experienced by a woman are consequential determinants of her health status. However, there is no published research comparing the patterns of subsequent pregnancy outcomes following a live birth, natural fetal loss, or induced abortion. Objectives: The objective of this study was to describe the characteristic patterns of subsequent pregnancy outcomes evolving from each of three initiating outcome events (birth, induced abortion, natural fetal loss) occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Recent research findings from the same study population also indicate that an abortion greatly increases the likelihood of another abortion in subsequent pregnancies, and that this tendency is found across all races, ethnicities, and age groups. 20 A low incidence of B-A-B sequences is consistent with these results since it requires an abortion to be followed by a live birth in a subsequent pregnancy, a sequence of pregnancy outcomes which is relatively uncommon.…”
Section: Discussionsupporting
confidence: 73%
“…Recent research findings from the same study population also indicate that an abortion greatly increases the likelihood of another abortion in subsequent pregnancies, and that this tendency is found across all races, ethnicities, and age groups. 20 A low incidence of B-A-B sequences is consistent with these results since it requires an abortion to be followed by a live birth in a subsequent pregnancy, a sequence of pregnancy outcomes which is relatively uncommon.…”
Section: Discussionsupporting
confidence: 73%
“…27 , 28 In a previous analysis, we determined that women 36 + years of age are increasingly more likely to abort a subsequent pregnancy and less likely to experience childbirth following an index abortion, no matter the pregnancy for which the abortion occurred. 23 The results of the current study also indicate that abortion is increasingly likely with increasing age and pregnancy order, independent of the first pregnancy outcome. Therefore, there is no reason to believe that the missing pregnancy outcomes in later reproductive years are a threat to the validity of our findings.…”
Section: Discussionsupporting
confidence: 60%
“…In a previous study, we determined that women who experience an abortion for any pregnancy in their reproductive history were more likely to become pregnant again and to experience another abortion in the next subsequent pregnancy. 23 We also found that 23% of Medicaid beneficiaries whose first pregnancy ended in an abortion were pregnant a second time within 12 months with approximately 60% undergoing a second abortion. 24 An important Finnish study followed a cohort of 1269 women who underwent chemical abortion for a follow-up period of 4.2 years ( + /− 1.5) and determined that young women with previous abortions were most likely to experience abortion in the subsequent pregnancy.…”
Section: Introductionmentioning
confidence: 57%
“…This finding is consistent with previous research which indicates that abortion results in a higher number of rapid repeat pregnancies which result in more abortions. 15,16 Within the group of women with both births and abortions, 38.5% had an abortion timed consistent with an attempt to delay a first birth, 17.9% had an abortion that spaced live births, and 52.3% had an abortion that could indicate a desire to end childbearing. The estimated period prevalence for each of these patterns is 2.2%, 1.0%, and 3.0% respectively.…”
Section: Discussionmentioning
confidence: 99%